Transcriptome and proteome analysis of Salmonella enterica serovar Typhimurium systemic infection of wild type and immune-deficient mice. - Olusegun Oshota; Max Conway; Maria Fookes; Fernanda Schreiber; Roy R Chaudhuri; Lu Yu; Fiona J E Morgan; Simon Clare; Jyoti Choudhary; Nicholas R Thomson; Pietro Lio; Duncan J Maskell; et al. (PLoS ONE)
Salmonella enterica are a threat to public health. Current vaccines are not fully effective. The ability to grow in infected tissues within phagocytes is required for S. enterica virulence in systemic disease. As the infection progresses the bacteria are exposed to a complex host immune response. Consequently, in order to continue growing in the tissues, S. enterica requires the coordinated regulation of fitness genes. Bacterial gene regulation has so far been investigated largely using exposure to artificial environmental conditions or to in vitro cultured cells, and little information is available on how S. enterica adapts in vivo to sustain cell division and survival. We have studied the transcriptome, proteome and metabolic flux of Salmonella, and the transcriptome of the host during infection of wild type C57BL/6 and immune-deficient gp91-/-phox mice. Our analyses advance the understanding of how S. enterica and the host behaves during infection to a more sophisticated level than has previously been reported.